A Study on the Feeding Practices among Under-Five Children in Urban Slum dwellers of District Dehradun, India (Bangladesh Journal of Medical Science, 2016)
Background: Breast milk feeding is the first fundamental right of the child. However, there are many cultural practices associated with infant feeding of which certain undesirable practices need to be discouraged.Objectives: To assess the feeding practices of under five year children in urban slum and to determine the factors influencing it, if any.Methodology: Community based analytical cross sectional study was conducted in urban slums amongst mothers over one-year period. A house to house survey was conducted and Data was collected using a pre-tested, structured questionnaire on breastfeeding practices & data pertaining to breastfeeding practices was asked in detail from mothers of babies who were breastfed.Results: A total of 381 children were studied. A total of 87.0% of the children were delivered at health facilities and the rest at home. 65.9% received prelacteal feed in the form of water, infant milk formula, cow milk and honey. Most of the children (54.1%) received breast milk within 24 hrs of birth. 95.0% received colostrum and 67.2% received exclusive breast feeding for 6 months. It was observed that children who were exclusively breastfed for six months were found to be better nourished (51.3%).Conclusions: Majority of the mothers were practicing exclusive breast feeding, however a significant proportion of children was deprived of timely initiation of breast feeding. About 2/3 of the mothers were still practicing pre-lacteal feeds to their children. The study documents that there was significantly increased risk of PEM if the child is not exclusive breastfed for 6 months.Bangladesh Journal of Medical Science Vol.15(1) 2016 p.15-19